Creating fiscal space for enhancing public investment in Sindh agriculture sector: A qualitative study of provincial spending in Pakistan - Rana, Abdul Wajid (International Food Policy Research Institute, 2019)
Agriculture and Irrigation sectors except for national food security and federal agriculture research have been devolved to the provinces following Eighteenth Constitutional Amendment in 2010. The Government of Sindh has approved and notified its first ever Agriculture and Livestock Policy in April 2018. To achieve objectives outlined in the Policy, it is imperative to increase investment in agriculture sector substantially to unleash the full potential of agriculture both for inclusive growth and economic development in the province. Moving towards this desirable goal of enhancing investment in agriculture and irrigation, it is vital to understand current resource sharing between the federation and federating units in Pakistan, gross resources available to the province in a financial year, dynamics of public expenditure allocations at sub-national level, and interplay of diverse interests during the budget process (Fan, Yu, and Saurkar 2008; Mogues 2015). Similarly, budget institutions, electoral system, and political institutions, apart from population composition, play their role in influencing public spending allocations during budget process and imposing constraints. The evidence suggests that budget process and institutions have substantial influence on budget allocation across different sub-regions and sectors. Despite huge transfer of resources to the provinces following the 7th National Finance Commission Award of 2010, the provinces have been underscoring increasing tight fiscal space. Given these pronounced binding constraint and rigid allocation of resources, it is challenging to enhance allocations to achieve desirable policy objectives. In these environments, insight regarding political and budget institutions will help in structural analysis of the budget, rationalization of existing public spending across sectors, and exploring the possibility of fiscal space through resource allocation restructuring. This paper reviews the interaction of political and administrative institutions, allocation of available resources as well as public spending trends and identify the fiscal space that could possibly be made available for enhanced allocation to agriculture, livestock, fisheries and irrigation in Sindh. Section 2 provides the structure of province of Sindh’s economy and various challenges confronting it. Section 3 reviews resources available, inter-mediation of budget institutions for resource allocation, public investment and structure of spending in Sindh; both recurrent and development. Section 4 highlights the subsidies in agriculture, particularly the subsidies on fertiliser, wheat farmers and millers, and irrigation. Section 5 looks at the taxes related to agricultural land and revenues collected. Section 6 estimates the fiscal space within existing resources that can be made available for enhanced investment in agriculture and irrigation.